Endodontic postoperative flare-up: An update - Sanaa Bassam (Elsevier, 2021)
Endodontic treatment corresponds to a combined chemical and mechanical approach, followed by a three dimensional hermetic obturation, that eliminate the pulpal and periradiculare disease and boost healing and repair of periradiculare tissue. Despite the advances in the endodontic field, the inter-appointment flare up remains a true nightmare that encounters every dentist. This complication commences a few hours or days after root canal procedures and it is characterized by the development of pain and/or swelling, requiring an unscheduled appointment for emergency treatment. Different studies showed that flare-ups represent a multifactorial phenomenon including mechanical, chemical and microbial factors. In addition, a correlation was found between flare-up and age, gender, tooth type, presence of preoperative pain, tooth condition before treatment, irrigation techniques, number of visits as well as intracanal medication. Moreover, some medicine intake was proved to be efficient in controlling this postoperative pain. However, a clear procedure to avoid its occurrence is yet to be established. In this review, we summarize knowledge about the etiology of flare-up and its related factors. This could be effective in helping dentists to adapt some strategies to prevent it.